Evidence for Persistent Heteroplasmy and Ancient Recombination in the Mitochondrial Genomes of the Edible Yellow Chanterelles From Southwestern China and Europe - Zhang, Ying; Wang, Shaojuan; Li, Haixia; Liu, Chunli; Mi, Fei; Wang, Ruirui; Mo, Meizi; Xu, Jianping (Frontiers in Microbiology, 2021)
Mitochondrial genes and genomes have patterns of inheritance that are distinctly different from those of nuclear genes and genomes. In nature, the mitochondrial genomes in eukaryotes are generally considered non-recombining and homoplasmic. If heteroplasmy and recombination exist, they are typically very limited in both space and time. Here we show that mitochondrial heteroplasmy and recombination may not be limited to a specific population nor exit only transiently in the basidiomycete Cantharellus cibarius and related species. These edible yellow chanterelles are an ecologically very important group of fungi and among the most prominent wild edible mushrooms in the Northern Hemisphere. At present, very little is known about the genetics and population biology of these fungia cross large geographical distances. Our study here analyzed a total of 363 specimens of edible yellow chanterelles from 24 geographic locations in Yunnan in southwestern China and six geographic locations in five countries in Europe. For each mushroom sample, we obtained the DNA sequences at two genes, one in the nuclear genome and one in the mitochondrial genome. Our analyses of the nuclear gene, translation elongation factor 1-alpha (tef-1) and the DNA barcode of C. cibarius and related species, suggested these samples belong to four known species and five potential new species. Interestingly, analyses of the mitochondrial ATP synthase subunit 6 (atp6) gene fragment revealed evidence of heteroplasmy in two geographic samples in Yunnan and recombination within the two new putative species in Yunnan. Specifically, all four possible haplotypes at two polymorphic nucleotide sites within the mitochondrial atp6 gene were found distributed across several geographic locations in Yunnan. Furthermore, these four haplotypes were broadly distributed across multiple phylogenetic clades constructed based on nuclear tef-1 sequences. Our results suggest that heteroplasmy and mitochondrial recombination might have happened repeatedly during the evolution of the yellow chanterelles. Together, our results suggest that the edible yellow chanterelles represent an excellent system from which to study the evolution of mitochondrial-nuclear genome relationships.